Το Δέντρο με τις Τρεις Φωνές: Αναθεωρώντας τα έμφυλα στερεότυπα στα κλασσικά παραμύθια των αδελφών Γκριμ - Μιχαήλ, Στυλιανή (My University, 2025)
This thesis examines the representation of gender roles in the classic fairy tales of the Brothers Grimm, focusing on Snow White and Cinderella. Through theoretical analysis and artistic research, it highlights the gender stereotypes perpetuated in these narratives. As a creative response, the original fairy tale The Tree with Three Voices was developed, offering a new narrative free from traditional gender structures, emphasizing self awareness, companionship, and inner exploration. The work is accompanied by original, abstract illustrations designed for an audience of adolescents and young adults. The thesis demonstrates how creative practice can serve as a space for reflection and subversion of cultural narratives, contributing to a contemporary reexamination of identity and gender.
Keywords: Classic fairytales; Gender roles; Gender stereotypes; Artistic research; Κλασικά παραμύθια; Έμφυλοι ρόλοι; Στερεότυπα φύλου